iNaturalist-facilitated rediscovery of Monarda mexicana (Lamiaceae) in high-elevation habitats of Durango, Mexico - Mckenzie, Patrick F.; Gallegos, Jesús Guadalupe González; Díaz, Perla Yalexcia Carrera (Phytotaxa, 2026)
Monarda mexicana, a taxon from the high-elevation Sierra Madre Occidental of Durango, Mexico, is rediscovered based on a recent observation from the community science platform iNaturalist. This observation led to targeted fieldwork, herbarium study, and cultivation. Two present-day, geographically isolated, high-elevation populations are documented, including a new specimen and two previously unrecognized historical collections. These populations exhibit diagnostic characters matching the original circumscription of M. mexicana, including exceptionally broad involucral bracts with acuminate apices, triangular-subulate calyx lobes, yellow pollen, distinctive corolla morphology, and characteristic vestiture. Plants cultivated from seed differ from Monarda citriodora var. austromontana in vegetative traits and belowground morphology. The morphological coherence, ecological specialization, and persistence of these populations support recognition of Monarda mexicana as a distinct species, rather than as a morphological extreme of M. citriodora var. austromontana. Recognition of M. mexicana has implications for conservation, as it appears to be restricted to a small number of isolated mountaintop localities.